2022
DOI: 10.3390/biom12081040
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Promoting ATAD2 and Its Preclinical Challenges

Abstract: ATAD2 has received extensive attention in recent years as one prospective oncogene with tumor-promoting features in many malignancies. ATAD2 is a highly conserved bromodomain family protein that exerts its biological functions by mainly AAA ATPase and bromodomain. ATAD2 acts as an epigenetic decoder and transcription factor or co-activator, which is engaged in cellular activities, such as transcriptional regulation, DNA replication, and protein modification. ATAD2 has been reported to be highly expressed in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 143 publications
0
4
0
Order By: Relevance
“…In breast cancer, ATAD2 has been identified as an ERα coregulatory factor that plays a critical role in ER-mediated activation. ATAD2 is directly associated with estrogen-bound ERα and ACTR, and thus elevates the expression of ERα-targeted cell cycle regulators, such as cyclin D1, Myc, and E2F1, which promote cancer cell proliferation [ 26 , 27 ]. Additionally, ATAD2 could positively mediate the expression of pro-survival genes, including SGK, VEGF, IRS2, and AKT, which contribute to promoting breast cancer progression [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, ATAD2 has been identified as an ERα coregulatory factor that plays a critical role in ER-mediated activation. ATAD2 is directly associated with estrogen-bound ERα and ACTR, and thus elevates the expression of ERα-targeted cell cycle regulators, such as cyclin D1, Myc, and E2F1, which promote cancer cell proliferation [ 26 , 27 ]. Additionally, ATAD2 could positively mediate the expression of pro-survival genes, including SGK, VEGF, IRS2, and AKT, which contribute to promoting breast cancer progression [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are two isoforms of human ATAD2, ATAD2A and ATAD2B ( 75 ). However, the majority of published functional studies have been performed on ATAD2A ( 21 , 75 , 76 ). ATAD2 is an emerging oncoprotein, a potential biomarker and a potent cancer drug target.…”
Section: The Bet Family: Brd4 Brd2 and Brd Testis Associated (Brdt)mentioning
confidence: 99%
“…Liu et al [46] have reviewed several studies that have reported that the ATAD2 can regulate different downstream molecules and is overexpressed in various cancer types, including BC, gastric cancer, pancreatic cancer, colorectal cancer, ovarian cancer, uterine corpus endometrial carcinoma, cervical cancer, prostate cancer, renal cancer, and lung cancer. Due to the fact that ATAD2 is a co-activator of the ERs and the androgen receptors in BC, it mediates the expression of E2 that induces cell proliferation and cell cycle progression in estrogen-dependent tumors [47].…”
Section: Plos Onementioning
confidence: 99%